1993
DOI: 10.1007/bf00180054
|View full text |Cite
|
Sign up to set email alerts
|

Solitary versus multiple cholesterol gallbladder stones

Abstract: The development and growth pattern of solitary and multiple cholesterol gallbladder stones was defined using cholecystography in a prospective study of 48 patients whose initial cholecystograms indicated a stone-free gallbladder and who developed gallstones within the subsequent 5 years. Radiological observations performed over 365 patient-years were complemented by macroscopic examination, radiograms, scanning electron microscopy, and chemical analysis of gallstones from these and other patients obtained at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…In human gallstone disease, highly correlated with gallbladder motor dysfunction (51), these crystals may accumulate in bile and provide the substrate for gallstone formation. The observed crystal morphologies correlate to scanning electron microscopy studies of human gallstones (52), showing a well-ordered arrangement of compact crystals in slowly growing solitary cholesterol gallstones. In contrast, in fast-growing multiple cholesterol stones, unsettled crystals forming random aggregates were found being radially arranged in a perpendicular position to the center of the hemisphere.…”
Section: Discussionsupporting
confidence: 70%
“…In human gallstone disease, highly correlated with gallbladder motor dysfunction (51), these crystals may accumulate in bile and provide the substrate for gallstone formation. The observed crystal morphologies correlate to scanning electron microscopy studies of human gallstones (52), showing a well-ordered arrangement of compact crystals in slowly growing solitary cholesterol gallstones. In contrast, in fast-growing multiple cholesterol stones, unsettled crystals forming random aggregates were found being radially arranged in a perpendicular position to the center of the hemisphere.…”
Section: Discussionsupporting
confidence: 70%
“…Bile acid composition of gallstones from man was also studied by Schoenfield et al (1966). The development and growth pattern of solitary and multiple cholesterol gallbladder stones has been studied in an informative paper of Wolpers and Hofmann (1993). Calcium salts have been observed in the nucleus (Bills and Lewis, 1975;Cowie et al, 1973) as well as in concentric layers suggesting the sequential growth of the gallstone (Kaufman et al, 1990;Gilloteaux et al, 1997).…”
Section: Gallstonesmentioning
confidence: 97%
“…Third, it did not always work. Research by the late Karlheinrich Wolpers in Germany 103 suggested that when acute cholecystitis occurred, a noncholesterol layer was deposited on the cholesterol gallstone, precluding or at least slowing dissolution. Furthermore, analyses of the natural history of gallstone disease indicated that the asymptomatic gallstone should not be treated.…”
Section: Dissolution Of Cholesterol Gallstones By Oral Bile Acid Admimentioning
confidence: 99%